Influence of crop planting ratio on the yield and quality of combined forage of corn-bambara nut grown under the tropical humid climate - Belel, Mustapha Dauda; Abd Halim, Mohd Ridzwan (Faculty of Engineering, Universiti Putra Malaysia, 2018)
The forage corn has been used as a feed resource for ruminant but it is low in crude protein content such that animals have to be supplemented with protein sources. An experiment was set up using corn intercropped with bambara nut landrace, Bambwus in a randomized complete block design to in order to investigate the contribution of different combination ratios (C4:B0, C4:B0+N, C3:B1, C2:B2, C1:B3, C0:B4) of corn with bambara on the quality of combined forage. Results from the study showed that crop growth rate, leaf chlorophyll and total leaf area were significantly higher among the intercrops compared to monocrop. Total dry matter yield was similar in all combinations. Sole corn had 73% neutral detergent fiber (NDF) which was higher than in the intercrops except C1:B3. Corn-bambara nut combinations ratios also differed significantly in NDF and acid detergent fiber (ADF). Protein in sole bambara nut was 14.8%. Among the combinations, crude protein was highest in C1:B3 (17.3%). Crude protein in sole corn was 8.52%. Lignin was highest in combinations with more bambara nut with sole bambara nut having 4.92% lignin. For improvement of overall forage quality, it is recommended that bambara nut be planted as an intercrop with corn at the ratio of 1 corn to 3 bambara nut.